The determinants of the impact of the split-share structure reform on the capital structure of Chinese listed firms - Pei, Lin (2017)
The purpose of study the determinants of capital structure is to interpret the various of financing methods employed by firms to finance the investment. In this case, corporations should select the best financing sources with consideration of all relevant factors to determine the optimal capital structure. The academic research in western countries on capital structure has developed into a relatively mature theory for nearly half century. However, the institutional environment between this countries and China is quite different. There are higher efficient capital markets, more perfect corporate governance system and external legal regulation in western countries than China. China is a developing country in transition economy, so the imperfect and lagging credit system, immature stock market and legal system make the capital structure of Chinese listed companies exist in a different mode compared to developing countries. Furthermore, the split-share structure reform started at 2005 has a significant influence on Chinese capital markets, thus, it is incentive for this research to study the factors of Chinese listed companies’ capital structure and whether these determinants has the same action mode before and after split share reform. This study utilizes debt ratio as the proxy for capital structure and capital structure measure consists of three group of independent variables, firm characteristics as first group including growth opportunity, profitability, size, tangibility, volatility, liquidity, non-debt tax shield, second group is macroeconomic conditions (i.e. GDP growth rate, inflation rate) and industry conditions (dummy variable) is last group. Panel data that included sample of Chinese A-share listed companies from 2002 to 2016 approach and three regression estimations (OLS, the fixed effect mode, the random effect model) were used to test the correlation between capital structure and independent variables. The sample period is separated to two parts: 2002-2005 and 2006-2016 in order to observe the variation before and after the reform. The results show some changes. Specifically, the firm size is strongly significant and positive associated with debt ratio than lower level of significant before the reform. Changing from insignificant to higher significantly negative relation is tangibility. While, non-debt tax shield is inconsistent with theoretical expectations, which has a positive significantly effect on capital structure. The variation of macroeconomic factors and industry factors is not obvious compared to two sample periods. Based on the research and limitations of this research, several recommendations are raised in section of conclusion, which might be beneficial for future research.